The contribution of being physically active to successful aging - Piccardi, Laura; Pecchinenda, Anna; Palmiero, Massimiliano; Giancola, Marco; Boccia, Maddalena; Giannini, Anna Maria; Guariglia, Cecilia (Frontiers in Human Neuroscience, 2023)
Growing old involves changes in physical, psychological, and cognitive functions. Promoting physical and mental health has become one of the priorities for an aging population. Studies have demonstrated the benefits of engaging in regular physical activity. Here, we aimed to understand the relationships between physical activity and working memory complaints in attention, memory storage, and executive functions. We hypothesized that physical activity was negatively associated with complaints in working memory domains after controlling for socio-demographics and distress factors, such as anxiety, stress, and depression. Two hundred and twenty-three individuals aged between 65 and 100 years (74.84; SD=7.74; 133 males) without self-reported neurological and/or psychiatric disorders completed a questionnaire on socio-demographic, with questions on physical activity and the Italian version of the working memory questionnaire (WMQ) and the DASS-21 measuring anxiety, stress, and depression. Results from three linear regression models showed that low physical activity was associated with complaints in attention (R 2 = .35) and executive functions (R 2 = .37) but not in memory storage (R 2 = .28). Notably, age, gender, and total emotional distress (DASS score) were significant in all regression models. Our results suggested regular physical activity, even just walking, is crucial for maintaining efficient cognitive function. Theoretical and practical implications for engaging in physical activity programs and social aggregation during exercise are considered. Limitations are also presented.